Systematic review of mediatization of politics in Southeast Asia - Kho, Suet Nie; Julia Wirza Zawawi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mediatization of politics refers to the meta-process by which political institutions are highly dependent and influenced by the usage of media in political processes. In the early 2000s, research was heavily pioneered by scholars from Western World. For the past decade, scholars from the Southeast Asian region have explored and used the concept in understanding the relationship between media and political institutions in their respective countries. However, there is no cohesive systematic review on research that has been done on how mediatization of politics is being constructed in Southeast Asian context. This is crucial to determine mediatization of politics claims as the new paradigm of media studies holds true in the context of Asian political systems. Therefore, the present article conducted a systematic literature review on mediatization of politics in the Asian region. This study integrated different research designs and the review was based on PRISMA 2020 (Preferred Reporting Items for Systematic and Meta Analysis 2020). From 45 articles initially screened, 9 articles were chosen for the final systematic review. Four themes emerged from the systematic review, namely a) democratization, b) disinformation, c) religious populism and d) nationalism. The results showed that in most SEA countries, political actors are embracing the high dependency of media, whether it is the mainstream media or the digital media. Along with the mediatization, comes positive and negative consequences that are different according to the history of the countries. Future scholars should focus on expanding and building the systematic review in different regions.